Bearing capacity of bucket foundations in silt-over-clay soil condition under combined V-H-M loading. Issue 12 (2nd December 2022) - Feng, Tugen; Zhou, Shujin; Zhou, Mi; Xu, Yun; Zhang, Xihong; Ye, Mingge
Abstract: The bearing capacity of bucket foundations subjected to combined vertical-horizontal-moment loadings ( V-H-M ) is an important issue for its design and application. This paper investigates the response of bucket foundations under V-H-M loadings in silt-over-clay using small strain finite element method. Model validation is carried out by comparing with previously testing data with good agreement obtained. Then parametric study is conducted to study the effect of embedded ratio, soil property and top layer thickness. It is found that the soil failure mechanism and corresponding bearing capacity of bucket foundations in silt-over-clay are significantly different to that in clay only condition. Approximating expressions are proposed to describe the unique trends of the normalized failure envelopes for bucket foundations in silt-over-clay soil deposits. The findings of this study could help to guide design application of bucket foundations.